Matrix metallopeptidase 3 coding SNPs suppress cell invasion in MCF7 breast cancer cells - Ahmad Suhaimi, Shafinah; Soon, Choy Chan; Chong, Pei Pei; Saad, Norazalina; Chau, De Ming; Rosli, Rozita (Penerbit Universiti Kebangsaan Malaysia, 2024)
Matrix metallopeptidase 3 (MMP3) is among the key players in breast cancer metastasis that contributes to the highest cancer-related deaths in females globally. Previously, in silico analyses had shown that several coding single nucleotide polymorphisms (SNPs) of MMP3 were predicted to alter the secondary structures of MMP3 and subsequently reduce its mRNA stability. To validate the mentioned hypotheses, this study aimed to determine the effects of six coding SNPs of MMP3 on its mRNA stability, protein expression level as well as cell invasiveness in vitro. In this study, breast adenocarcinoma MCF7 cells were transfected with MMP3 wild type (MMP3-WT) and a variant containing SNPs (MMP3-Var). Following transfection, protein expression level, mRNA stability and enzyme activity of MMP3-WT and MMP3-Var were evaluated. Finally, the effect of MMP3 coding SNPs on cell invasiveness in breast cancer was determined. In this study, the mRNA stability, protein expression level and enzymatic activity of MMP3-Var were significantly reduced. Moreover, the presence of MMP3 coding SNPs led to attenuated invasiveness of transfected MCF7 cells. In conclusion, these findings may contribute to the current understanding of these coding SNPs with metastasis in breast cancer.